2022
DOI: 10.15252/embr.202255503
|View full text |Cite
|
Sign up to set email alerts
|

TRAPPC1 is essential for the maintenance and differentiation of common myeloid progenitors in mice

Abstract: Myeloid cell development in bone marrow is essential for the maintenance of peripheral immune homeostasis. However, the role of intracellular protein trafficking pathways during myeloid cell differentiation is currently unknown. By mining bioinformatics data, we identify trafficking protein particle complex subunit 1 (TRAPPC1) as continuously upregulated during myeloid cell development. Using inducible ER‐TRAPPC1 knockout mice and bone marrow chimeric mouse models, we demonstrate that TRAPPC1 deficiency causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In the meantime, TRAP-PIII was known to play an important role in autophagy and was found in the preautophagosomal structure [50]. TRAPP is composed of 10 subunits, and Trappc1 is one of the main members of the TRAPP family [28,51]. In our study, we found that Trappc1 deficiency in naive T cells significantly increased the ER to Golgi transport defect and UPR pathway with upregulated intracellular Ca 2+ level, and ER stress-related genes such as Atf4 and Chop.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In the meantime, TRAP-PIII was known to play an important role in autophagy and was found in the preautophagosomal structure [50]. TRAPP is composed of 10 subunits, and Trappc1 is one of the main members of the TRAPP family [28,51]. In our study, we found that Trappc1 deficiency in naive T cells significantly increased the ER to Golgi transport defect and UPR pathway with upregulated intracellular Ca 2+ level, and ER stress-related genes such as Atf4 and Chop.…”
Section: Discussionsupporting
confidence: 50%
“…We purchased CD45.1 + C57BL/6J (B6) background mice from Beijing University Experimental Animal Center. Trappc1 loxp/loxp mice and ER‐Cre mice were kindly provided by Dr. Lianfeng Zhang of the Institute of Laboratory Animal Science [28]. We also obtained CD4‐cre mice from Dr. Baojun Zhang of Xi'an Jiaotong University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEPs (Lin − Sca1 − c-Kit + CD34 − CD16/32 - ), CMPs (Lin − Sca1 − c-Kit + CD34 hi CD16/32 - ), and GMPs (Lin − Sca1 − c-Kit + CD34 hi CD16/32 hi ) were detected by flow cytometry with a gating strategy ( Figure S6 B). 32 , 33 Our results showed that the percentages and cell numbers of CMPs and GMPs were significantly lower in the bone marrow of tamoxifen-treated ER-Rictor KO mice compared to tamoxifen-treated WT mice, while no significant changes in MEPs were detected in tamoxifen-treated ER-Rictor KO mice ( Figures 2 A–2C). MDPs are generally thought to yield monocyte-committed progenitors, known as cMoPs, which further develop into mature monocytes.…”
Section: Resultsmentioning
confidence: 68%